2018
DOI: 10.2196/rehab.7805
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Digital and Remote Communication Technologies as a Tool for Multiple Sclerosis Management: Narrative Review

Abstract: Despite recent advances in multiple sclerosis (MS) care, many patients only infrequently access health care services, or are unable to access them easily, for reasons such as mobility restrictions, travel costs, consultation and treatment time constraints, and a lack of locally available MS expert services. Advances in mobile communications have led to the introduction of electronic health (eHealth) technologies, which are helping to improve both access to and the quality of health care services. As the Intern… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
95
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(98 citation statements)
references
References 84 publications
(117 reference statements)
1
95
0
2
Order By: Relevance
“…It is possible that this is because patients are receiving PT in the community; although this is not reflected by the survey results. It can also be argued that a contemporary health system has several possibilities how to best support people with long term disabilities through the use of alternative approaches such as the education of patients to self-manage their own condition or the use of electronic health technologies [31]. Telerehabilitation approaches including interactive web-based programs, home-based systems for physical activity monitoring, or online communities [36], for instance, could monitor and motivate patients over time, whilst potentially improving the accessibility and quality of physiotherapy services [31].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that this is because patients are receiving PT in the community; although this is not reflected by the survey results. It can also be argued that a contemporary health system has several possibilities how to best support people with long term disabilities through the use of alternative approaches such as the education of patients to self-manage their own condition or the use of electronic health technologies [31]. Telerehabilitation approaches including interactive web-based programs, home-based systems for physical activity monitoring, or online communities [36], for instance, could monitor and motivate patients over time, whilst potentially improving the accessibility and quality of physiotherapy services [31].…”
Section: Discussionmentioning
confidence: 99%
“…These applications aim at assisting conventional paraclinical methods and can have significant benefits for patients, their caregivers, and healthcare providers. These benefits are important because MS requires ongoing treatment and monitoring (Marziniak et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A telephone-based cognitive-behavioral therapy for family caregivers of people with dementia increased their mental and physical health as well as coping abilities (Wilz, Reder, Meichsner, & Soellner, 2017). Marziniak et al (2018) argued that digital applications and remote communication technology for patients with MS increased rapidly in recent years for reasons such as mobility restrictions, travel costs, consultation and treatment time constraints, and a lack of locally available MS expert services. Mahmoodi, Mohammad Khani, Ghobari Banab, and Bagheri (2016) reported that group cognitive-behavioral therapy could increase the use of compatible strategies for coping with stress and decrease the use of incompatible strategies.…”
mentioning
confidence: 99%
“…These applications aim at completing conventional inter-clinical methods and can have significant benefits for patients and healthcare providers. These benefits are essential because MS requires ongoing treatment and monitoring (Marziniak et al, 2018).…”
Section: Introductionmentioning
confidence: 99%